Prolonged and flexible primary moult overlaps extensively with breeding in beach‐nesting Hooded Plovers Thinornis rubricollis. (20th August 2014) - Rogers, Ken G.; Rogers, Danny I.; Weston, Michael A.; Reneerkens, Jeroen
<x xml:space="preserve">Abstract</x> We present the first report of complete overlap of breeding and moult in a shorebird. In southeastern Australia, Hooded Plovers Thinornis rubricollis spend their entire lives on oceanic beaches, where they exhibit biparental care. Population moult encompassed the 6‐month breeding season. Moult timing was estimated using the Underhill–Zucchini method for Type 2 data with a power transformation to accommodate sexual differences in rates of moult progression in the early and late stages of moult. Average moult durations were long in females (170.3 ± 14.2 days), and even longer in males (210.3 ± 13.5 days). Breeding status was known for most birds in our samples, and many active breeders (especially males) were also growing primaries. Females delayed the onset of primary moult but were able to increase the speed of moult and continue breeding, completing moult at about the same time as males. The mechanism by which this was achieved appeared to be flexibility in moult sequence. All moult formulae fell on one of two linked moult sequences, one faster than the other. The slower sequence had fewer feathers growing concurrently and also had formulae indicating suspended moults. Switching between sequences via common formulae is possible at many points during the moult cycle, and three of 12 recaptures were confirmed to have switched sequences in the same moult season. Hooded Plovers thus have a prolonged primary moult with the flexibility to change their rate of moult; this may facilitate high levels of replacement clutches that are associated with passive nest defence and low reproductive success.